Lumbar spinal loads and muscle activity during a golf swing - Lim, Y. T.; Chow, J. W.; Chae, W. S. (Sports Biomechanics, 2012)
This study estimated the lumbar spinal loads at the L4-L5 level and evaluated electromyographic (EMG) activity of right and left rectus abdominis, external and internal obliques, erector spinae, and latissimus dorsi muscles during a golf swing. Four super VHS camcorders and two force plates were used to obtain three-dimensional (3D) kinematics and kinetics of golf swings performed by five male collegiate golfers. Average EMG levels for different phases of golf swing were determined. An EMG-assisted optimization model was applied to compute the contact forces acting on the L4-L5. The results revealed a mean peak compressive load of over six times the body weight (BW) during the downswing and mean peak anterior and medial shear loads approaching 1.6 and 0.6 BW during the follow-through phases. The peak compressive load estimated in this study was high, but less than the corresponding value (over 8 BW) reported by a previous study. Average EMG levels of different muscles were the highest in the acceleration and follow-through phases, suggesting a likely link between co-contractions of paraspinal muscles and lumbar spinal loads.